2017
DOI: 10.1111/jog.13274
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between umbilical resistance index and fetal growth: Pilot study

Abstract: In normal pregnancies there seems to be a linear relationship between umbilical RI measured at 31-34 weeks of gestation and average fetal growth in the third trimester. The greater the resistance index, the lower the weight gain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 14 publications
0
5
2
Order By: Relevance
“…Further, Ebbing et al 11 reported a progressive increase of UVBF during the third trimester in pregnancies complicated by fetal macrosomia. Conversely, the previously reported occurrence of a low pulsatility index in the uterine or umbilical arteries in macrosomic fetuses was not confirmed in our population despite an observed lower but non‐significant trend in such fetuses 12,14‐17,32 . Similarly, our data do not confirm the reported association between cerebroplacental ratio and fetal weight 33 …”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…Further, Ebbing et al 11 reported a progressive increase of UVBF during the third trimester in pregnancies complicated by fetal macrosomia. Conversely, the previously reported occurrence of a low pulsatility index in the uterine or umbilical arteries in macrosomic fetuses was not confirmed in our population despite an observed lower but non‐significant trend in such fetuses 12,14‐17,32 . Similarly, our data do not confirm the reported association between cerebroplacental ratio and fetal weight 33 …”
Section: Discussioncontrasting
confidence: 99%
“…Conversely, the previously reported occurrence of a low pulsatility index in the uterine or umbilical arteries in macrosomic fetuses was not confirmed in our population despite an observed lower but non-significant trend in such fetuses. 12,[14][15][16][17]32 Similarly, our data do not confirm the reported association between cerebroplacental ratio and fetal weight. 33 Prospective design, inclusion of consecutive pregnancies, large sample size, assessment of umbilical vein hemodynamic for all the included cases and statistical analysis adjusted for all the main possible confounders represent the main strengths of this study.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…The highest prevalence was reported by Yoon et al, who reported a prevalence of AEDF or REDF of 2.13% amongst 328 unselected-risk women in South Korea [38]. The four studies (898 women) conducted in lower middle-income countries (Bangladesh, Papua New Guinea, Nigeria and Tunisia) did not report any cases of AEDF or REDF [39][40][41][42]. Similarly, a three-country prospective cohort study of 431 healthy, low-risk women by Drukker et al in Brazil, Kenya and the UK identified no AEDF cases in any country [29].…”
Section: Resultsmentioning
confidence: 91%